2002
DOI: 10.1021/jp026314l
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Phase Behavior of the (EO)13(PO)30(EO)13(Pluronic L64)/Water/p-Xylene System Using MesoDyn

Abstract: The phase behavior of the (EO) 13 (PO) 30 (EO) 13 (Pluronic L64)/water/p-xylene system in the mesoscopic region was investigated using MesoDyn, a new dynamic density functional method. The "equivalent chain" method was used to perform the parametrization of the Gaussian chain. In this paper, we compare the mesoscopic morphology formations of systems at different concentrations of solvents and discuss the effect of water on the formation of micelles. The calculated results show that Pluronic L64 does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…However, the micelles are not perfectly spherical. Interestingly, the imperfect spherical micelles are formed during the simulation, which has been reported in the literatures [34,52,59]. When the concentration ascends to 50 vol%, the rod-like micelles are found.…”
Section: Resultssupporting
confidence: 69%
“…However, the micelles are not perfectly spherical. Interestingly, the imperfect spherical micelles are formed during the simulation, which has been reported in the literatures [34,52,59]. When the concentration ascends to 50 vol%, the rod-like micelles are found.…”
Section: Resultssupporting
confidence: 69%
“…The molecular structure of F127 is separated into two types of beads (E, P), where seven EO segments and four PO segments represent one E bead and one P bead, respectively. According to previous studies on the partial volumes of EO groups and PO groups (Vlimmeren et al, 1999;Guo et al, 2002), it ensures that the EO and PO beads have comparable sizes of 450 Å 3 . Therefore, the nominal formula and coarsegained chains of F127 used in this study are shown in Fig.…”
Section: Simulation System and Parametersmentioning
confidence: 99%
“…Since Ag-64, F127 and water molecule were selected to be the simulated targets; the mixing free energies and FloryHuggins parameters (χ) could be obtained by solubility parameter as following: [35] …”
Section: Dynamic Light Scattering Measurementmentioning
confidence: 99%